Volume 4: Heat Transfer; Electric Power; Industrial and Cogeneration 1995
DOI: 10.1115/95-gt-149
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Experimental/Computational Study of Flow in Turbine Blade Cooling Passage: Part II — Numerical Simulations

Abstract: A combined experimental/computational study has been performed for flow in rotating serpentine passages which approximate internal cooling passage for turbine blades. Experimental results are presented in the companion, Part I. The numerical simulations were performed using detailed experimental velocity profile measurements, documented in Part I, to set inflow conditions. Incompressible flow predictions with a two-layer k-ε turbulence model, which isolated the Coriolis induced secondary flow, agreed well with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Thus, buoyancy further increases heat transfer at the high pressure surface while suppressing that at the low pressure surface. Compressible flow simulations, McGrath and Tse (1994), show that the total effect of Coriolis and buoyancy forces lead to an increase in streamwise velocity to 1.4U, along the high pressure surface and this yields an increase in Nu by 30%, which is still short of the 100% measured by . However, it can be inferred from the present experimental results that the convection of cool fluid from the center of the passage toward the high pressure surface by Coriolis induced secondary flows greatly increases the temperature difference between the wall and the coolant.…”
Section: Relationship To Heat Transfermentioning
confidence: 89%
See 3 more Smart Citations
“…Thus, buoyancy further increases heat transfer at the high pressure surface while suppressing that at the low pressure surface. Compressible flow simulations, McGrath and Tse (1994), show that the total effect of Coriolis and buoyancy forces lead to an increase in streamwise velocity to 1.4U, along the high pressure surface and this yields an increase in Nu by 30%, which is still short of the 100% measured by . However, it can be inferred from the present experimental results that the convection of cool fluid from the center of the passage toward the high pressure surface by Coriolis induced secondary flows greatly increases the temperature difference between the wall and the coolant.…”
Section: Relationship To Heat Transfermentioning
confidence: 89%
“…Due to entrance effect, the streamwise velocities on the leading side are higher than those on the trailing side. McGrath and Tse (1994) show that the high velocity discharged from the trailing side of the delivery pipe is deflected onto the leading side of the model upon impact with the plenum wall. The flow entering the model is angled toward the leading side and this gives rise to the resulting high velocities on that side.…”
Section: Concave Surfacementioning
confidence: 95%
See 2 more Smart Citations
“…They indicated that either a low Reynolds number k -c model, two-layer k -c model or second-moment closure model is needed for accurate prediction of flow and heat transfer for this complex flaw situation. McGrath and Tse (1995) performed the computation on the four pass, serpentine passage with three 180° turns which is identical to that of Wagner et al (1991) using the kc turbulence model with two wall treatments: the generalized wall function and the classical Van-Driest mixing length formulation. The two-layer wall integration turbulence model provides improvement over the wall function simulation.…”
Section: Introductionmentioning
confidence: 99%